Biofeedback system in remotely monitored exercise program in pregnant women with obesity: a pre-experimental research - Diana Bernardo; Carlos Carvalho; Raquel Leirós Rodrígues; Cristina Martins; Joana Morais; Jorge Mota; Paula Clara Santos (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objectives: E-health programs may be an excellent strategy to overcome some barriers related to the non-practice of exercise among pregnant women with obesity. This study aims to present a monitored exercise program for pregnant women with obesity using the Sword Phoenix® biofeedback system; and to evaluate pregnant women's perception of the biofeedback system and the exercise program protocol. Methods: A pre-experimental research was done through a One-shot case study design. Twelve pregnant women with Body Mass Index ≥ 30 kg/m2, were invited to perform for two weeks a home-based structured exercise program protocol with a digital biofeedback system, during exercise the women used an accelerometer to measure the intensity of the exercises. At the end of the two-week exercise period, the pregnant women filled in a questionnaire to assess their perception of usability, satisfaction, safety and motivation regarding exercise program and biofeedback system. Results: The accelerometry results indicate that, during the exercise program protocol, the pregnant women spent 79.3% of the time in moderate activities. The adherence to the program had an average performance of 40%. The results of the questionnaire demonstrated that 100% (n=12) of the participants enjoyed the system and recognized it as a safe instrument with the potential to increase physical activity during pregnancy.